A Method for Traffic Calming Using Radio Transmitter - Amin Mirza Boroujerdian; Samane Sheikhy (Journal of Advanced Transportation)
Excessive speed is one of the major factors in transportation safety assessment and is influenced by road geometric design, vehicle properties, and driving pattern. Exploiting innovative methods along with the conventional ones has been proven to be effective in road safety to control the speed limit. In this study, a supplementary tool is introduced to help drivers to observe the speed limit. In line with this objective, the effectiveness of Voice Sign System (VSS) as an Intelligent Transportation System is evaluated. In order to measure the speed, video processing software is used. Moreover, SPSS is utilized to perform statistical analysis and compare upstream and downstream speeds before and after a message transmission. The study is conducted in Yadegar-e-Imam expressway, located in Tehran, to evaluate the effectiveness of a voice message. The message reads as follows: “Observe the Speed Limit.” The results reveal that VSS is an effective tool for speed reduction as well as the speed limit observation in expressways. The study shows that the speed is reduced by 18% on average, and speed limit observation is improved by 46.5%, out of which 18.2% is direct and 28.3% is indirect influence of VSS.